“There is no compulsion in religion” - Deringil, Selim (2000)
This essay is a preliminary attempt to place nineteenth century Ottoman conversion policies in a comparative context in relation to both earlier Ottoman centuries and other imperial polities, viz.: the Spanish and Russian. The present study has three aims. First, to ask some practical questions about the fact and nature of the conversion process. Second, to try to ascertain whether there is some pattern to the various cases occurring in the archival documentation for the turbulent years between the declaration of the Tanzimat in 1839 and the Reform Edict of 1856. And third, to put the late Ottoman attitude to conversion and apostasy into a broader comparative framework than has hitherto been attempted.This paper is the first fruit of a larger project that will examine conversion and apostasy in the late Ottoman Empire from the Tanzimat era through to the end of the Empire in 1918.